Children's literature in context - McCulloch, Fiona (London : Continuum, 2011)
Children's Literature in Context is a clear, accessible and concise introduction to children's literature andǩts wider contexts. It begins by introducing key issues involved in the study of children's literature and its social, cultural and literary contexts. Close readings of commonly studied texts including Lewis Carroll's Alice books, The Wonderful Wizard of Oz, The Lion, the Witch and the Wardrobe, the Harry Potter series and the His Dark Materials trilogy highlight major themes and ways of reading children's literature.
Includes bibliographical references (p. 159-167) and index.
Keywords: Children's literature, English -- History and criticism; Children's literature, American -- History and criticism